Hak dan Kewajiban Suami Istri Perspektif Hukum Islam - Matondang, Fatiha Sabila Putri; Lubis, Anisah; Lubis, Ahmad Ilman; Siregar, Pangundian; Alvionita, Riza (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Abstract